Promising study of the impact of medical qigong as compared with usual care to improve the QoL of cancer patients - Oh, B.; Butow, P.; Mullan, Barbara; Clarke, S.; Beale, P.; Pavlakis, N.; Kothe, E.; Lam, L.; Rosenthal, D. (John Wiley & Sons Ltd., 2010)
Aim: To evaluate, in a RCT, the use of medical qigong (MQ) compared with usual care to improve the QoL of cancer patients. Design: RCT. Setting: Medical Oncology Departments in three large university teaching hospitals in Australia. Participants: Patients who had a confirmed diagnosis of malignancy at any stage, were aged 18 years and older and had an expected survival length of 12 months or more were recruited in the waiting room. Intervention: A modified traditional qigong programme developed and delivered by the first author, an experienced MQ instructor. The programme was run for 10 weeks. Each session (assumed to be once a week, but this is not explicitly stated) consisted of 15 min discussion of health issues, 30 min stretching and body movement in standing postures, 15 min movement in a seated posture, and 30 min meditation including breathing exercises. The control group received usual care. Main outcome measures: QoL: Functional Assessment of Cancer Therapy – General (FACT-G) and Functional Assessment of Cancer Therapy – Fatigue (FACT-F); mood: Profile of Mood State (POMS); and the inflammatory biomarker C-reactive protein.Main results: There were no significant differences in measurements between the intervention and control groups at baseline. Participants in the MQ group reported larger improvements in QoL than in the usual care group and had significantly greater improvements in fatigue. They also had a greater reduction in mood changes overall and on four subscales (tension and anxiety, depression, lack of vigour and fatigue), but there were no changes with respect to anger and hostility and confusion. Finally, participants in the MQ group had significant differences in the level of the inflammation biomarker. Author's conclusion: ‘The findings of this study are positive and provide evidence that MQ is safe and effective in improving QOL, fatigue, mood status and reducing symptoms, side-effects and inflammation in cancer patients.’